The role of plant growth promoting rhizobacteria in strengthening plant resistance to fluoride toxicity: a review - Singh, Anamika; Yadav, Virendra Kumar; Gautam, Hemant; Rathod, Lokendra; Chundawat, Rajendra Singh; Singh, Gulab; Verma, Rakesh Kumar; Sahoo, Dipak Kumar; Patel, Ashish (Frontiers in Microbiology, 2023)
A wide variety of bacteria are present in soil but in rhizospheric area, the majority of microbes helps plant in defending diseases and facilitate nutrient uptake. These microorganisms are supported by plants and they are known as plant growth-promoting rhizobacteria (PGPR). The PGPRs have the potential to replace chemical fertilizers in a way that is more advantageous for the environment. Fluoride (F) is one of the highly escalating, naturally present contaminants that can be hazardous for PGPRs because of its antibacterial capacity. The interactions of F with different bacterial species in groundwater systems are still not well understood.However, the interaction of PGPR with plants in the rhizosphere region reduces the detrimental effects of pollutants and increases plants' ability to endure abiotic stress. Many studies reveal thatPGPRshave developedF defencemechanisms, which include efflux pumps, Intracellular sequestration, enzyme modifications, enhanced DNA repair mechanism, detoxification enzymes, ion transporter/ antiporters, F riboswitches, and genetic mutations. These resistance characteristics are frequently discovered by isolating PGPRs from high F-contaminated areas or by exposing cells to fluoride in laboratoryconditions. Numerous studies have identified F-resistant microorganisms that possess additional F transporters and duplicates of the well-known targets of F. Plants are prone to F accumulation despite the soil's low F content, which may negatively affect their growth and development. PGPRs can be used as efficient F bioremediators for the soil environment.Environmental biotechnology focuses on creating genetically modified rhizobacteria that can degradeF contaminants over time.The present review focuses on a thorough systemic analysis of contemporary biotechnological techniques, such as gene editing and manipulation methods, for improving plant-microbe interactions for F remediation and suggests the importance of PGPRs in improving soil health and reducing the detrimental effects of F toxicity. The most 3 recent developments in the realm of microbial assistance in the treatment of F-contaminated environments are also highlighted.